Method for preparing porous silicon carbon negative electrode material with good conductivity from photovoltaic silicon crystal waste
By preparing photovoltaic silicon crystal waste into nanoscale porous silicon particles and building a core-shell structure, the problem of insufficient volume expansion and conductivity of silicon-based anode materials during charging and discharging is solved, and efficient battery performance improvement and cost reduction are achieved.
Patent Information
- Application Number
- CN202411325304.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The volume expansion of the silicon-based negative electrode material during charging and discharging leads to unstable electrode structure, unstable interface structure of solid electrolytes, and poor conductivity.
By pulverizing photovoltaic silicon crystal waste into nano-scale porous silicon particles, and building a carbon skeleton support for TiO2 coating and N crosslinking, a core-shell structure is built, including an outer amorphous carbon coating layer and a sub-outer conductive TiO2 layer. The carbon skeleton of the layer and inner coral structure improves conductivity and alleviates the volume expansion effect.
It effectively improves the conductivity of silicon-carbon negative electrode materials, extends the cycle life of the battery, improves high-rate discharge performance, reduces production costs, and promotes the development of the circular economy.
Smart Images

Figure CN119240706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic silicon crystal waste treatment, and in particular to a method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste. Background Art
[0002] As the requirements for battery energy density in electric vehicles and high-performance consumer electronics products increase, silicon-based negative electrode materials are expected to have broad application prospects in the next generation of high-energy density batteries due to their high specific capacity and good electrochemical properties. The advantages of silicon-based negative electrode materials are as follows: 1. High theoretical specific capacity. The theoretical specific capacity of silicon is as high as about 4200mAh / g, which far exceeds the 372mAh / g of traditional graphite negative electrodes. Its high capacity comes from the fact that silicon atoms can form lithium compounds Li with 4.4 lithium ions. 4.4 1. Silicon has significantly increased the amount of energy that can be stored per unit mass of material. Silicon-based negative electrode materials can greatly increase the energy density of lithium-ion batteries, thereby extending the battery life or reducing the size of the battery, and promoting the development of industries such as portable electronic devices and electric vehicles. 2. Low voltage platform. The lithium embedding voltage platform of silicon is relatively low, about 0.4V (relative to the lithium electrode). The low voltage platform means that the silicon-based negative electrode has less energy loss during the charging and discharging process, which helps to improve the overall energy efficiency of the battery. 3. It is rich in resources and has the advantage of low cost.
[0003] With the steady development of my country's photovoltaic industry, waste photovoltaic silicon crystal materials contain a large amount of high-purity block silicon materials. The silicon in solar panels is usually high-purity polycrystalline silicon or monocrystalline silicon. Compared with silicon materials purified from raw materials, recycled silicon has advantages in material purity and structural consistency. Silicon materials are abundant and low in cost. Compared with other high-capacity negative electrode materials, the cost advantage of silicon materials makes it feasible in large-scale production, which helps to reduce battery manufacturing costs. Although silicon-based negative electrode materials have shown great potential in lithium-ion batteries, they still face many challenges and problems in their practical applications, including the following aspects:
[0004] 1. Instability of electrode structure due to volume expansion: Silicon expands and collapses by ~300% during the charge and discharge process. This significant volume change can cause the breakage and pulverization of silicon-based materials, which in turn leads to damage to the electrode structure, rapid capacity decay, and reduced cycle life of silicon-based negative electrode materials. 2. Instability of solid electrolyte interface structure (SEI): Due to the repeated exposure of silicon surface to electrolyte during the lithium insertion-extraction process, SEI is repeatedly broken and regenerated. Unstable SEI consumes a large amount of electrolyte and lithium ions, reduces coulomb efficiency, and accelerates the decay of battery performance. Unstable SEI increases the frequency of side reactions and leads to irreversible capacity loss. 3. Poor conductivity: The intrinsic electronic conductivity of silicon materials is low, making it difficult to conduct current effectively, especially at high rate discharge. Low conductivity limits the charge and discharge rate performance of silicon-based negative electrode materials. And it is still a challenge to build a stable and efficient conductive network in silicon-based materials, especially during long-term cycles, when the conductive network may be destroyed due to volume expansion. Summary of the invention
[0005] The present invention aims to provide a method for preparing a porous silicon-carbon negative electrode material with good conductivity from photovoltaic silicon crystal waste, so as to solve the problem that the volume expansion of the current silicon-based negative electrode material during the charging and discharging process will lead to unstable electrode structure, unstable solid electrolyte interface structure, and poor conductivity.
[0006] To achieve the above object, the present invention provides a method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste, comprising:
[0007] Step 1: Preparation of micron-sized silicon particles: ball milling bulk photovoltaic silicon crystal waste material, preliminary crushing, and reducing the particle size to micron level;
[0008] Step 2: Preparation of micron-sized porous silicon particles: dissolving the micron-sized silicon particles in a water-soluble strong acid to remove the metal oxides embedded in the ball milling process and the metal on the surface of the photovoltaic silicon crystal, followed by filtering and washing to obtain a porous silicon particle material;
[0009] Step 3: Preparation of nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton: the obtained micron-scale porous silicon particles are configured into a slurry, and sand-milled to reduce the particle size, and graphene and high molecular organic matter are mixed into the sand-milled nano-scale porous silicon particle slurry to form a carbon skeleton; after stirring and mixing, nitrogen-containing compounds and titanium-containing compounds are added to construct an N-crosslinked organic skeleton and a TiO2 conductive layer, and stirred and mixed again to obtain a nano-scale porous silicon slurry coated with TiO2 and supported by a N-crosslinked carbon skeleton, and the slurry is further dried and crushed to obtain nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton;
[0010] Step 4: Preparation of porous silicon-carbon negative electrode particles with good conductivity: Nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton are mixed with a carbon-containing compound and a B-containing sintering aid and then sintered in a rotary kiln to construct an outermost amorphous carbon coating layer.
[0011] It is further defined that in step 1, ball milling is used to reduce the size of photovoltaic silicon crystal waste, Si3N4 is used as the ball milling medium, and ZnO is added to the ball mill jar at the same time, and the ball mill jar is protected by inert gas; the ball milling speed is 800 rpm, and the ball milling time is 20 to 28 hours; in this process, the mass ratio of photovoltaic silicon crystal waste, ZnO, and ball milling medium is 1:0.5:120.
[0012] It is further defined that in step 1, the ball milling medium is Si3N4 with a diameter of 0.1 to 0.2 mm, and the ZnO particle size is 200 nm to 400 nm.
[0013] It is further defined that in step 2, the micron-sized silicon particles are dissolved in a hydrochloric acid solution having a concentration of 1 M, and stirred at a stirring heating temperature of 40° C. and a stirring speed of 100 to 500 rpm, preferably 150 rpm, and react for 1 hour and then filter.
[0014] It is further defined that the organic solvent in the sand milling process of step 3 is 99% ethanol, the dispersing solvent is an organic solvent, the organic solvent is a compound of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethyleneimine with different weight average molecular weights, the mass ratio of the dispersing solvent to the silicon powder is 1:2.5, the sand milling time is 8 to 12 hours, and the size D of the porous silicon powder after sand milling is 90 The particle size is 200-800 nm, and more preferably 200 nm. A nano-scale porous silicon particle slurry is prepared. During the sand milling process, the dispersion stability of the particles can be further improved by the action of the dispersion solvent and the sand milling medium.
[0015] Further defined, in step 3, a nano-scale porous silicon particle slurry is obtained, a dispersing solvent is added to the slurry, and graphene and single-walled carbon nanotube materials are added to construct a carbon skeleton, the graphene and single-walled carbon nanotubes are compounded at a mass ratio of 1:80 to obtain a carbon skeleton, the mass ratio of nano-scale porous silicon particles, dispersing solvent, and carbon material is 1:0.5:8, and then sand-milled for 4 to 8 hours to construct a carbon skeleton, and the size D of the porous silicon is 90 Keep it at the nano level.
[0016] It is further defined that after obtaining the nano-scale porous silicon particle slurry supported by the carbon skeleton in step 3, a nitrogen-containing compound and a titanium-containing compound are added, and stirred to obtain a nano-scale porous silicon slurry supported by a carbon skeleton coated with TiO2 and cross-linked by N, the stirring speed is 120rpm, the reaction time is 1h, and the stirring temperature is 80°C. The nitrogen-containing compound includes: urea, aniline and melamine, and the mass ratio of urea, aniline and melamine is 1:0.8:8. The titanium-containing compound includes tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate, and the mass ratio of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate is 1:4:4, and the mass ratio of silicon powder to organic titanium source is 1:0.2.
[0017] It is further defined that in step 3, the nano-scale porous silicon slurry coated with TiO2 and supported by N-crosslinked carbon skeleton is granulated by spray drying, and the spray drying feed temperature is 120° C., the outlet air temperature is 80° C., and the air flow rate is 2 m / s.
[0018] It is further defined that the amorphous carbon in step 4 is formed by thermal decomposition of carbon-containing organic matter and B-containing sintering aid under high temperature conditions, and the heating rate of the sintering process is 5°C / min. The sintering temperature is 800°C. The high temperature reaction time is 1h. Natural cooling and cooling, the furnace speed is 4r / min. An inert gas containing hydrogen is introduced, the inert gas is argon or nitrogen, and the inert gas delivery flow rate is controlled at 1.5L / min. The gas delivery flow ratio of inert gas to hydrogen is 10:1. The carbon-containing organic matter is a complex of epoxy resin, asphalt and citric acid, and the epoxy resin, asphalt and citric acid are 1:3:6 by mass. The sintering aid is lithium borate (LiBO2) lithium borate (Li2B4O7) and boron oxide (B2O3) in a mass ratio of 1:8:8. The mass ratio of TiO2-coated and N-crosslinked carbon skeleton-supported nano-porous silicon particles, carbon-containing organic matter, and B-containing sintering aid is 200:1:0.6. During the reaction, inert gas argon needs to be introduced as a protective gas, and a small amount of hydrogen is introduced at the same time to adjust the decomposition process of the carbon source, control the deposition rate and morphology of carbon, promote the cracking of the carbon source, and prevent excessive deposition.
[0019] The present invention also provides a porous silicon-carbon negative electrode material with good electrical conductivity, having a core-shell structure, and including, from the outside to the inside: an outer layer, a sub-outer layer and an inner layer, wherein the outer layer is a boron-doped amorphous carbon coating layer, the sub-outer layer is a TiO2 coating layer, and the inner layer is a coral structure, wherein high-strength graphene and single-walled carbon nanotubes construct a carbon skeleton structure, and N cross-links form an electron path.
[0020] Principle of the present invention: Carbon material composite: Through the amorphous carbon coating layer on the outer layer of the core-shell structure and the carbon skeleton inside, the highly conductive carbon material can provide a high-speed transmission path for electrons. After composite, the carbon-carbon interface has good contact and can effectively transfer electrons, alleviating the volume expansion problem of silicon; Silicon particle nano- and porous processing: Nano-sized silicon particles can shorten the diffusion path of lithium ions and electrons and reduce the resistance during the transmission process. In addition, the porous structure can reduce the volume stress of the material and reduce the risk of material pulverization; Doping: Through strategies such as boron doping in the outer layer of the core-shell structure and constructing an N cross-linked structure in the inner layer, the electronic band structure of silicon is changed, the carrier concentration is increased, and the conductivity of the material is improved; Surface coating of conductive materials: The secondary outer layer of the core-shell structure is composed of conductive TiO2, and the coating layer can provide a good electron transmission path. Its coating effect can protect silicon particles from electrolyte erosion and extend the cycle life of the battery.
[0021] Advantages of the present invention:
[0022] 1. The raw materials of the silicon-carbon negative electrode particles prepared by the present invention are derived from photovoltaic silicon crystal waste. The high-net-value utilization of photovoltaic silicon-based waste is conducive to promoting the development of the circular economy, reducing production costs, improving market competitiveness, and enhancing supply chain resilience;
[0023] 2. The overall preparation process of the present invention has strong industrial compatibility and a simple process flow;
[0024] 3. A silicon-carbon negative electrode material with good conductivity was prepared by constructing a porous structure, building an N-crosslinked carbon skeleton, coating a conductive metal oxide layer, doping, and amorphous carbon coating. The material has a core-shell structure, with an amorphous carbon coating layer as the outermost layer, a conductive metal oxide layer as the second outermost layer, and a coral-like structure as the innermost layer. The N-crosslinked graphene carbon skeleton plays a supporting role, and nano-scale porous silicon particles are embedded in it. This structure can effectively alleviate the volume expansion effect of the material, improve conductivity, improve the high-rate discharge performance of the battery, and extend the cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a schematic flow chart of a method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The following is further described in detail through specific implementation methods:
[0027] The present invention uses waste crystalline silicon as raw material. Considering that the silicon material in the solar panel has undergone multiple process treatments, the processing process does not require overly complicated purification and processing steps, and can be directly used for further processing and modification, simplifying the manufacturing process, reducing costs, and promoting the coordinated development of the new energy industry and the battery industry. A carbon negative electrode material with a core-shell structure is constructed, and the outermost layer is a boron-doped amorphous carbon coating layer, which effectively improves the conductivity of the material and weakens the volume expansion. The second outer layer is a TiO2 coating layer, the purpose of which is to improve the good electron transmission path, prevent direct contact between silicon and the electrolyte, construct a stable SEI film layer, and reduce side reactions. The interior is a coral structure, and the high-strength graphene and single-walled carbon nanotubes construct a carbon skeleton structure, N cross-linking forms an electron path, and the embedded porous silicon particle structure can effectively control the volume expansion and improve the conductivity of the material. Its specific preparation method is shown in the attached Figure 1 shown.
[0028] Embodiment 1:
[0029] Step 1: Preparation of micron-sized silicon particles:
[0030] The size of photovoltaic silicon crystal waste is reduced by ball milling. Si3N4 is selected as the ball milling medium. ZnO is added to the ball mill jar at the same time. ZnO is used as a pore former. The pore former will generate pores during the grinding process to improve the porosity of the material. At the same time, inert gas such as argon or nitrogen is introduced into the ball mill jar for protection. The ball milling speed is 800rpm and the ball milling time is 28h. In this process, the mass ratio of photovoltaic silicon crystal waste, ZnO and ball milling medium is 1:0.5:120. Specifically, in this embodiment, the ball milling medium is Si3N4 beads with a size distribution of 0.1 to 0.2 mm. The ZnO used in ball milling is used as a pore former, and its particle size distribution is within 200nm to 400nm. The size of the silicon powder after ball milling is D 90 is 1um.
[0031] Step 2: Preparation of micron-sized porous silicon particles:
[0032] The micron-sized silicon particles are dissolved in a water-soluble strong acid to remove the metal oxides embedded in the ball milling process and the metal on the surface of the photovoltaic silicon crystal, and then filtered and washed to obtain a porous silicon particle material. In this embodiment, a hydrochloric acid solution with a concentration of 1M is used, the acid immersion time is 1h, the magnetic stirring heating temperature is 40°C, the stirring speed is 100-500rpm, preferably 150rpm, and the porous silicon particle material is obtained by filtering after stirring.
[0033] Step 31: The obtained micron-sized porous silicon particles are configured into a slurry, and the particle size is reduced by sand grinding. The organic solvent in the sand grinding process is 99% ethanol, the dispersing solvent is an organic solvent, and the organic solvent is a compound composed of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine with different weight average molecular weights. In this embodiment, polyvinyl pyrrolidone with a weight average molecular weight of 50,000, polyethylene glycol with a weight average molecular weight of 5,500, polyvinyl acid with a weight average molecular weight of 8,000, and polyethylene imine with a weight average molecular weight of 40,000 are selected. The mass ratio of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine is 1:2:2:1, and the mass ratio of the dispersing solvent to the silicon powder is 1:2.5. The sand grinding time is 12 hours. The size D of the porous silicon powder after sand grinding is 90 The particle size of the nanoporous silicon particles is 100 nm, and a nanoscale porous silicon particle slurry is prepared.
[0034] Step 32: Graphene and high molecular weight organic matter are mixed into the sand-milled nanoporous silicon particle slurry to form a carbon skeleton. The dispersion solvent in this step is the same as the dispersion solvent in step 31. In this step, graphene and single-walled carbon nanotube materials are specifically added to construct the carbon skeleton. Graphene and single-walled carbon nanotubes are compounded at a mass ratio of 1:80 to obtain a carbon skeleton. The mass ratio of nanoporous silicon particles, dispersion solvent, and carbon material is 1:0.5:8. Then sand-mill for 8 hours to construct the carbon skeleton. The size D of the porous silicon is 1:1. 90 Keep it within the nanometer level, specifically 200nm.
[0035] Step 33: After stirring and mixing, add nitrogen-containing compounds and titanium-containing compounds to construct N-crosslinked organic skeletons and TiO2 conductive layers. First, add nitrogen-containing compounds, which include: urea, aniline and melamine, and the mass ratio of urea, aniline and melamine is 1:0.8:8. Stirring is performed by magnetic stirring, the stirring speed is controlled at 120 rpm, the reaction time is preferably 1 hour, and the temperature during stirring is 80°C.
[0036] Subsequently, a titanium-containing compound was added to introduce a TiO2 coating layer, and the mixture was stirred to obtain a nano-scale porous silicon slurry coated with TiO2 and supported by a N-crosslinked carbon skeleton. The stirring speed was 120 rpm, the reaction time was 1 h, the stirring temperature was 80 ° C, the mass ratio of silicon powder to organic titanium source was 1:0.2, and the titanium-containing compounds included tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate. Tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate were compounded in a mass ratio of 1:4:4.
[0037] Step 34: The TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon slurry is spray-dried and granulated, the spray drying feed temperature is 120°C, the outlet air temperature is 80°C, and the air flow rate is 2m / s; the slurry is further dried and crushed to obtain TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon particles.
[0038] Step 4: Preparation of porous silicon-carbon negative electrode particles with good electrical conductivity: Nano-scale porous silicon particles coated with TiO2 and supported by a carbon skeleton cross-linked with N are mixed with carbon-containing compounds and B-containing sintering aids and then sintered in a rotary kiln to construct an outermost amorphous carbon coating layer. Amorphous carbon is formed by thermal decomposition of carbon-containing organic matter and B-containing sintering aids under high temperature conditions. The heating rate of the sintering process is 5°C / min, the sintering temperature is 800°C, the high-temperature reaction time is 1h, and the temperature is naturally cooled. The furnace speed is 4r / min, and an inert gas containing hydrogen is introduced. The inert gas is argon or nitrogen. The inert gas flow rate is controlled at 1.5L / min, and the gas flow ratio of the inert gas to hydrogen is 10:1. The carbon organic matter is a complex of epoxy resin, asphalt and citric acid, which are compounded in a mass ratio of 1:3:6. The sintering aid is a complex of lithium borate (LiBO2), lithium borate (Li2B4O7) and boron oxide (B2O3) in a mass ratio of 1:8:8. The mass ratio of TiO2-coated and N-crosslinked carbon skeleton-supported nano-porous silicon particles, carbon-containing organic matter and B-containing sintering aid is 200:1:0.6.
[0039] Embodiment 2:
[0040] Step 1: Preparation of micron-sized silicon particles:
[0041] The size of photovoltaic silicon crystal waste is reduced by ball milling. Si3N4 is selected as the ball milling medium. ZnO is added to the ball mill jar at the same time. ZnO is used as a pore former. The pore former will generate pores during the grinding process to improve the porosity of the material. At the same time, inert gas such as argon or nitrogen is introduced into the ball mill jar for protection. The ball milling speed is 800rpm and the ball milling time is 24h. In this process, the mass ratio of photovoltaic silicon crystal waste, ZnO and ball milling medium is 1:0.5:120. Specifically, in this embodiment, the ball milling medium is Si3N4 beads with a size distribution of 0.1 to 0.2 mm. The ZnO used in ball milling is used as a pore former, and its particle size distribution is within 200nm to 400nm. The size of the silicon powder after ball milling is D 90 It is 1.6um.
[0042] Step 2: Preparation of micron-sized porous silicon particles:
[0043] The micron-sized silicon particles are dissolved in a water-soluble strong acid to remove the metal oxides embedded in the ball milling process and the metal on the surface of the photovoltaic silicon crystal, and then filtered and washed to obtain a porous silicon particle material. In this embodiment, a hydrochloric acid solution with a concentration of 1M is used, the acid immersion time is 1h, the magnetic stirring heating temperature is 40°C, the stirring speed is 150rpm, and the porous silicon particle material is obtained by filtering after stirring.
[0044] Step 31: The obtained micron-sized porous silicon particles are configured into a slurry, and the particle size is reduced by sand grinding. The organic solvent in the sand grinding process is 99% ethanol, the dispersing solvent is an organic solvent, and the organic solvent is a compound composed of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine with different weight average molecular weights. In this embodiment, polyvinyl pyrrolidone with a weight average molecular weight of 50,000, polyethylene glycol with a weight average molecular weight of 5,500, polyvinyl acid with a weight average molecular weight of 8,000, and polyethylene imine with a weight average molecular weight of 40,000 are selected. The mass ratio of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine is 1:2:2:1, and the mass ratio of the dispersing solvent to the silicon powder is 1:2.5. The sand grinding time is 10 hours. The size D of the porous silicon powder after sand grinding is 90 The particle size of the nanoporous silicon particles is 400 nm, and a nanoscale porous silicon particle slurry is prepared.
[0045] Step 32: Graphene and high molecular weight organic matter are mixed into the sand-milled nanoporous silicon particle slurry to form a carbon skeleton. The dispersion solvent in this step is the same as the dispersion solvent in step 31. In this step, graphene and single-walled carbon nanotube materials are specifically added to construct the carbon skeleton. Graphene and single-walled carbon nanotubes are compounded at a mass ratio of 1:80 to obtain a carbon skeleton. The mass ratio of nanoporous silicon particles, dispersion solvent, and carbon material is 1:0.5:8. Then sand-mill for 6 hours to construct the carbon skeleton. The size D of the porous silicon is 1:1. 90 Keep it within the nanometer range, specifically 600nm.
[0046] Step 33: After stirring and mixing, nitrogen-containing compounds and titanium-containing compounds are added to construct N-crosslinked organic skeletons and TiO2 conductive layers. First, nitrogen-containing compounds are added. The nitrogen-containing compounds include: urea, aniline and melamine. The mass ratio of urea, aniline and melamine is 1:0.8:8. Stirring is performed by magnetic stirring. The stirring speed is controlled at 120 rpm. The reaction time is 1 hour. The temperature during stirring is 80°C.
[0047] Subsequently, a titanium-containing compound was added to introduce a TiO2 coating layer, and the mixture was stirred to obtain a nano-scale porous silicon slurry coated with TiO2 and supported by a N-crosslinked carbon skeleton. The stirring speed was 120 rpm, the reaction time was 1 h, the stirring temperature was 80 ° C, the mass ratio of silicon powder to organic titanium source was 1:0.2, and the titanium-containing compounds included tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate. Tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate were compounded in a mass ratio of 1:4:4.
[0048] Step 34: The TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon slurry is spray-dried and granulated, the spray drying feed temperature is 120°C, the outlet air temperature is 80°C, and the air flow rate is 2m / s; the slurry is further dried and crushed to obtain TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon particles.
[0049] Step 4: Preparation of porous silicon-carbon negative electrode particles with good electrical conductivity: Nano-scale porous silicon particles coated with TiO2 and supported by a carbon skeleton cross-linked with N are mixed with carbon-containing compounds and B-containing sintering aids and then sintered in a rotary kiln to construct an outermost amorphous carbon coating layer. Amorphous carbon is formed by thermal decomposition of carbon-containing organic matter and B-containing sintering aids under high temperature conditions. The heating rate of the sintering process is 5°C / min, the sintering temperature is 800°C, the high-temperature reaction time is 1h, and the temperature is naturally cooled. The furnace speed is 4r / min, and an inert gas containing hydrogen is introduced. The inert gas is argon or nitrogen. The inert gas flow rate is controlled at 1.5L / min, and the gas flow ratio of the inert gas to hydrogen is 10:1. The carbon organic matter is a complex of epoxy resin, asphalt and citric acid, which are compounded in a mass ratio of 1:3:6. The sintering aid is a complex of lithium borate (LiBO2), lithium borate (Li2B4O7) and boron oxide (B2O3) in a mass ratio of 1:8:8. The mass ratio of TiO2-coated and N-crosslinked carbon skeleton-supported nano-porous silicon particles, carbon-containing organic matter and B-containing sintering aid is 200:1:0.6.
[0050] Embodiment 3:
[0051] Step 1: Preparation of micron-sized silicon particles:
[0052] The size of photovoltaic silicon crystal waste is reduced by ball milling. Si3N4 is selected as the ball milling medium. ZnO is added to the ball mill jar at the same time. ZnO is used as a pore former. The pore former will generate pores during the grinding process to improve the porosity of the material. At the same time, inert gas such as argon or nitrogen is introduced into the ball mill jar for protection. The ball milling speed is 800rpm and the ball milling time is 20h. In this process, the mass ratio of photovoltaic silicon crystal waste, ZnO and ball milling medium is 1:0.5:120. Specifically, in this embodiment, the ball milling medium is Si3N4 beads with a size distribution of 0.1 to 0.2 mm. The ZnO used in ball milling is used as a pore former, and its particle size distribution is within 200nm to 400nm. The size of the silicon powder after ball milling is D 90 It is 2um.
[0053] Step 2: Preparation of micron-sized porous silicon particles:
[0054] The micron-sized silicon particles are dissolved in a water-soluble strong acid to remove the metal oxides embedded in the ball milling process and the metal on the surface of the photovoltaic silicon crystal, and then filtered and washed to obtain a porous silicon particle material. In this embodiment, a hydrochloric acid solution with a concentration of 1M is used, the acid immersion time is 1h, the magnetic stirring heating temperature is 40°C, the stirring speed is 150rpm, and the porous silicon particle material is obtained by filtering after stirring.
[0055] Step 31: The obtained micron-sized porous silicon particles are configured into a slurry, and the particle size is reduced by sand grinding. The organic solvent in the sand grinding process is 99% ethanol, the dispersing solvent is an organic solvent, and the organic solvent is a compound composed of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine with different weight average molecular weights. In this embodiment, polyvinyl pyrrolidone with a weight average molecular weight of 50,000, polyethylene glycol with a weight average molecular weight of 5,500, polyvinyl acid with a weight average molecular weight of 8,000, and polyethylene imine with a weight average molecular weight of 40,000 are selected. The mass ratio of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethylene imine is 1:2:2:1, and the mass ratio of the dispersing solvent to the silicon powder is 1:2.5. The sand grinding time is 8 hours. The size D of the porous silicon powder after sand grinding is 90 The particle size of the nanoporous silicon particles is 800 nm, and a nanoscale porous silicon particle slurry is prepared.
[0056] Step 32: Graphene and high molecular weight organic matter are mixed into the sand-milled nanoporous silicon particle slurry to form a carbon skeleton. The dispersion solvent in this step is the same as the dispersion solvent in step 31. In this step, graphene and single-walled carbon nanotube materials are specifically added to construct the carbon skeleton. Graphene and single-walled carbon nanotubes are compounded at a mass ratio of 1:80 to obtain a carbon skeleton. The mass ratio of nanoporous silicon particles, dispersion solvent, and carbon material is 1:0.5:8. Then sand-mill for 4 hours to construct the carbon skeleton. The size D of the porous silicon is 1:1. 90 Keep it at the micron level, specifically 1um.
[0057] Step 33: After stirring and mixing, nitrogen-containing compounds and titanium-containing compounds are added to construct N-crosslinked organic skeletons and TiO2 conductive layers. First, nitrogen-containing compounds are added. The nitrogen-containing compounds include: urea, aniline and melamine. The mass ratio of urea, aniline and melamine is 1:0.8:8. Stirring is performed by magnetic stirring. The stirring speed is controlled at 120 rpm. The reaction time is 1 hour. The temperature during stirring is 80°C.
[0058] Subsequently, a titanium-containing compound was added to introduce a TiO2 coating layer, and the mixture was stirred to obtain a nano-scale porous silicon slurry coated with TiO2 and supported by a N-crosslinked carbon skeleton. The stirring speed was 120 rpm, the reaction time was 1 h, the stirring temperature was 80 ° C, the mass ratio of silicon powder to organic titanium source was 1:0.2, and the titanium-containing compounds included tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate. Tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate were compounded in a mass ratio of 1:4:4.
[0059] Step 34: The TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon slurry is spray-dried and granulated, the spray drying feed temperature is 120°C, the outlet air temperature is 80°C, and the air flow rate is 2m / s; the slurry is further dried and crushed to obtain TiO2-coated and N-crosslinked carbon skeleton-supported nano-scale porous silicon particles.
[0060] Step 4: Preparation of porous silicon-carbon negative electrode particles with good electrical conductivity: Nano-scale porous silicon particles coated with TiO2 and supported by a carbon skeleton cross-linked with N are mixed with carbon-containing compounds and B-containing sintering aids and then sintered in a rotary kiln to construct an outermost amorphous carbon coating layer. Amorphous carbon is formed by thermal decomposition of carbon-containing organic matter and B-containing sintering aids under high temperature conditions. The heating rate of the sintering process is 5°C / min, the sintering temperature is 800°C, the high-temperature reaction time is 1h, and the temperature is naturally cooled. The furnace speed is 4r / min, and an inert gas containing hydrogen is introduced. The inert gas is argon or nitrogen. The inert gas flow rate is controlled at 1.5L / min, and the gas flow ratio of the inert gas to hydrogen is 10:1. The carbon organic matter is a complex of epoxy resin, asphalt and citric acid, which are compounded in a mass ratio of 1:3:6. The sintering aid is a complex of lithium borate (LiBO2), lithium borate (Li2B4O7) and boron oxide (B2O3) in a mass ratio of 1:8:8. The mass ratio of TiO2-coated and N-crosslinked carbon skeleton-supported nano-porous silicon particles, carbon-containing organic matter and B-containing sintering aid is 200:1:0.6.
[0061] Comparative Example 1:
[0062] The difference from Example 1 is that no pore-forming agent is added during the ball milling process, that is, no ZnO is added in step 1, and the rest of the preparation method and parameters are consistent with Example 1.
[0063] Comparative Example 2:
[0064] The difference from Example 1 is that no carbon skeleton structure is constructed, that is, no graphene and single-walled carbon nanotubes are added in step 3.2), and the rest of the preparation method and parameters are consistent with Example 1.
[0065] Comparative Example 3:
[0066] The difference from Example 1 is that the TiO2 coating layer and the N cross-linked structure are not constructed, that is, titanium-containing organic matter and nitrogen-containing organic matter are not introduced in step 3.3), and the rest of the preparation method and parameters are consistent with Example 1.
[0067] Comparative Example 4:
[0068] The difference from Example 1 is that no amorphous carbon-coated layered structure is constructed, that is, no carbon source organic matter and sintering aid are introduced in step 4), and the rest of the preparation method and parameters are consistent with Example 1.
[0069] The silicon-based negative electrode particles obtained in the above examples and comparative examples are further used to prepare negative electrodes, which specifically includes the following steps:
[0070] 1) The prepared silicon-based negative electrode particles, acetylene black, and sodium carboxymethyl cellulose are prepared into a slurry in a mass ratio of 7:1.5:1.5, and deionized water and anhydrous ethanol are selected as the solvent in a volume ratio of 8:2 to prepare a uniform slurry with a viscosity of 5800 mPa.S; the slurry is filtered and evenly coated on a Cu foil, the temperature during the coating process is 80°C, the vacuum drying oven is kept at a constant temperature of 90°C, dried for 6 hours, rolled, and then punched into a negative electrode sheet with a diameter of 10 mm.
[0071] 2) The prepared electrode was used as the negative electrode, and the NCM811 ternary material was selected as the positive electrode to complete the button assembly process, and the electrochemical performance of the assembled battery was tested.
[0072] The performance of the silicon-based negative electrode prepared from the materials obtained in Examples 1-3 and Comparative Examples 1-4 was tested, and the test method was as follows:
[0073] (1) DC resistance: Test standard: DCR (DC resistance) is obtained by testing at room temperature (25°C), battery capacity state 50%, 2C, and discharge for 20s.
[0074] (2) First coulombic efficiency test: voltage range 0.001 ~ 3V. Charge and discharge current: 0.1C, discharge first then charge. First coulombic efficiency calculation method: first charge capacity / first discharge capacity.
[0075] (3) Rate performance test method: Charge and discharge at rates of 0.1C, 0.2C, 0.4C, 0.8C, and 1.6C, with a voltage range of 0.001-3V, for 10 cycles each time, and discharge at a rate of 0.2C for 100 cycles to test its capacity retention rate.
[0076] (4) Cyclic performance test method: Discharge at 0.5C and 2C rates, with a voltage range of 0.001-3V, and cycle 800 times to test its capacity retention rate.
[0077] The electrical performance test results of the batteries prepared with the materials of Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.
[0078] Table 1 Battery performance test data
[0079]
[0080]
[0081] As can be seen from Example 1 and Comparative Example 1, the ball milling process is to add a pore-forming agent to improve the porosity of the material. The porous structure can reduce the volume stress of the material and reduce the risk of material pulverization. The nano-sized silicon particles can shorten the diffusion path of lithium ions and electrons and reduce the resistance during the transmission process. Because the powder particle size in Example 1 is relatively low, its impedance value is at the lowest value in Examples 1-3. As can be seen from Example 1 and Comparative Example 2, the material has a coral structure inside, and the high-strength graphene and single-walled carbon nanotubes construct a carbon skeleton structure, N cross-linking forms an electronic pathway, and the embedded porous silicon particle structure can effectively control the volume expansion and improve the conductivity of the material. As can be seen from Example 1 and Comparative Example 3, a TiO2 coating layer and a N cross-linking structure are constructed to change the electronic band structure of silicon, improve a good electronic transmission path, prevent silicon from directly contacting the electrolyte, construct a stable SEI film layer, and reduce side reactions. As can be seen from Example 1 and Comparative Example 4, the amorphous carbon coating layer on the outer layer of the core-shell structure effectively improves the conductivity of the material and weakens the volume expansion. The surface is coated with conductive material, and the sub-outer layer of the core-shell structure is composed of conductive TiO2. This coating layer can provide a good electron transmission path. Its coating effect can protect silicon particles from electrolyte corrosion and extend the cycle life of the battery.
[0082] The raw materials of silicon-carbon negative electrode particles prepared by the present invention are derived from photovoltaic silicon crystal waste. The high net value utilization of photovoltaic silicon-based waste is carried out, which is conducive to promoting the development of circular economy, reducing production costs, improving market competitiveness, and enhancing supply chain resilience; the overall preparation process of the present invention has strong industrial compatibility and simple process flow; by constructing a porous structure, building a N-crosslinked carbon skeleton, coating a conductive metal oxide layer, doping, and amorphous carbon coating, a silicon-carbon negative electrode material with good electrical conductivity is prepared. The material has a core-shell structure, the outermost layer is an amorphous carbon coating layer, the second outer layer is a conductive metal oxide layer, and the innermost layer is a coral-like structure. The N-crosslinked graphene carbon skeleton plays a supporting role, and nano-scale porous silicon particles are embedded therein. This structure can effectively alleviate the volume expansion effect of the material, improve conductivity, improve the high-rate discharge performance of the battery, and extend the cycle life.
[0083] Those skilled in the art can use other reagents with similar properties and similar reaction parameters mentioned in this application according to actual conditions, which will not be described in detail.
[0084] The above is only an embodiment of the present invention, and the common sense such as the known specific technical scheme and / or characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical scheme of the present invention, several modifications and improvements can be made, such as simply changing the rotation speed and time of the ball milling, simply changing the size of the ball milling medium, the ratio of ball milling media of different sizes, and the ratio of the medium to photovoltaic silicon crystal waste and the pore-forming agent, etc. In the present invention, unless otherwise clearly specified and limited, the terms "install", "connect", "connect", "fix" and the like should be understood in a broad sense, for example, it can be a fixed connection, or a detachable connection, or an integral connection; it can be directly connected, or indirectly connected through an intermediate medium, or it can be the internal connection of two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to the specific circumstances. The scope of protection claimed by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste, characterized in that: include: Step 1: Preparation of micron-sized silicon particles: ball milling bulk photovoltaic silicon crystal waste material, preliminary crushing, and reducing the particle size to micron level; Step 2: Preparation of micron-sized porous silicon particles: dissolving the micron-sized silicon particles in a water-soluble strong acid to remove the metal oxides embedded in the ball milling process and the metal on the surface of the photovoltaic silicon crystal, followed by filtering and washing to obtain a porous silicon particle material; Step 3: Preparation of nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton: the obtained micron-scale porous silicon particles are configured into a slurry, and sand-milled to reduce the particle size, and graphene and high molecular organic matter are mixed into the sand-milled nano-scale porous silicon particle slurry to form a carbon skeleton; after stirring and mixing, nitrogen-containing compounds and titanium-containing compounds are added to construct an N-crosslinked organic skeleton and a TiO2 conductive layer, and stirred and mixed again to obtain a nano-scale porous silicon slurry coated with TiO2 and supported by a N-crosslinked carbon skeleton, and the slurry is dried and crushed to obtain nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton; Step 4: Preparation of porous silicon-carbon negative electrode particles with good conductivity: Nano-scale porous silicon particles coated with TiO2 and supported by a N-crosslinked carbon skeleton are mixed with a carbon-containing compound and a B-containing sintering aid and then sintered in a rotary kiln to construct an outermost amorphous carbon coating layer.
2. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 1, characterized in that: In step 1, ball milling is used to reduce the size of photovoltaic silicon crystal waste, Si3N4 is used as the ball milling medium, and ZnO is added to the ball mill jar at the same time, and the ball mill jar is protected by inert gas; the ball milling speed is 200-1000rpm, and the ball milling time is 20-28h; in this process, the mass ratio of photovoltaic silicon crystal waste, ZnO, and ball milling medium is 1:0.5:
120.
3. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 2, characterized in that: In the step 1, the size distribution of the ball milling medium Si3N4 is 0.1-0.2 mm, and the particle size of the ZnO is 200 nm-400 nm.
4. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 1, characterized in that: In the step 2, the micron-sized silicon particles are dissolved in a hydrochloric acid solution with a concentration of 1 M, and stirred at a stirring heating temperature of 40° C. and a stirring speed of 100 to 500 rpm. After reacting for 1 hour, the mixture is filtered.
5. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 1, characterized in that: The organic solvent in the sand-milling process of step 3 is 99% ethanol, the dispersing solvent is an organic solvent, and the organic solvent is a compound composed of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl acid, and polyethyleneimine with different weight-average molecular weights. The mass ratio of the dispersing solvent to the silicon powder is 1:2.5, and the sand-milling time is 8 to 12 hours. The size D of the porous silicon powder after sand-milling is 90 The particle size is 200-800 nm, and a nano-scale porous silicon particle slurry is prepared.
6. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 5, characterized in that: In the step 3, a nano-scale porous silicon particle slurry is obtained, a dispersion solvent is added to the slurry, and graphene and single-walled carbon nanotube materials are added to construct a carbon skeleton. The graphene and single-walled carbon nanotubes are compounded at a mass ratio of 1:80 to obtain a carbon skeleton, and the mass ratio of the nano-scale porous silicon particles, the dispersion solvent, and the carbon material is 1:0.5:8, and then sand-milled for 4 to 8 hours to construct the carbon skeleton. The size D of the porous silicon 90 Keep it within the nanometer level.
7. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 6, characterized in that: After obtaining the carbon skeleton supported nano-scale porous silicon particle slurry in the step 3, nitrogen-containing compounds and titanium-containing compounds are added, and stirred to obtain TiO2-coated and N-crosslinked carbon skeleton supported nano-scale porous silicon slurry, the stirring speed is 100-300rpm, the reaction time is 0.5-2h, and the stirring temperature is 80°C. The nitrogen-containing compounds include urea, aniline and melamine, and the mass ratio of urea, aniline and melamine is 1:0.8:
8. The titanium-containing compounds include tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate. Tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate are compounded in a mass ratio of 1:4:4, and the mass ratio of silicon powder to organic titanium source is 1:0.
2.
8. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 7, characterized in that: In the step 3, the nano-scale porous silicon slurry coated with TiO2 and supported by N-crosslinked carbon skeleton is granulated by spray drying, the spray drying feed temperature is 120°C, the outlet air temperature is 80°C, and the air flow rate is 2m / s.
9. The method for preparing a porous silicon-carbon negative electrode material with good electrical conductivity from photovoltaic silicon crystal waste according to claim 1, characterized in that: In the step 4, amorphous carbon is formed by thermal decomposition of carbon-containing organic matter and B-containing sintering aid under high temperature conditions. The heating rate of the sintering process is 5°C / min, the sintering temperature is 800°C, the high-temperature reaction time is 1h, and the temperature is naturally cooled. The furnace speed is 4r / min, and an inert gas containing hydrogen is introduced. The inert gas is argon or nitrogen. The inert gas supply flow rate is controlled at 1.5L / min, and the supply flow rate ratio of the inert gas to hydrogen is 10:
1. The carbon-containing organic matter is a complex of epoxy resin, asphalt and citric acid, which are compounded in a mass ratio of 1:3:
6. The sintering aid is a complex of lithium borate, lithium borate and boron oxide in a mass ratio of 1:8:
8. The mass ratio of nano-scale porous silicon particles coated with TiO2 and supported by a carbon skeleton cross-linked by N, carbon-containing organic matter, and B-containing sintering aid is 200:1:0.
6.
10. A porous silicon-carbon negative electrode material with good electrical conductivity, characterized in that: It has a core-shell structure, and includes, from the outside to the inside: an outer layer, a sub-outer layer and an inner layer, wherein the outer layer is a boron-doped amorphous carbon coating layer, the sub-outer layer is a TiO2 coating layer, and the inner layer is a coral structure. The high-strength graphene and single-walled carbon nanotubes construct a carbon skeleton structure, and N cross-links form an electron path.
Citation Information
Patent Citations
Porous silicon / carbon composite negative electrode material of lithium ion battery, preparation method of porous silicon / carbon composite negative electrode material and lithium ion battery
CN114695887A
Cited By
Lithium ion solid-state battery negative electrode material and preparation method thereof
CN120089709A
Secondary battery and preparation method thereof, energy storage battery pack and electric equipment
CN120199762A
Secondary battery and preparation method thereof, energy storage battery pack and electrical equipment
CN120199762B
Three-dimensional cross structure silicon-carbon composite material based on photovoltaic silicon sludge as well as preparation method and application of three-dimensional cross structure silicon-carbon composite material
CN121641925A
